PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL)TERHADAP KEMAMPUAN BERFIKIR KRITIS SISWA PADA PEMBELAJARAN IPAS DI KELAS V SD NEGERI LAMKLAT - Dori Amina; Haris Munandar; Meriza Faradilla (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the implementation of the Problem Based Learning (PBL) model on students’ critical thinking skills in science and social learning (IPAS) in the fifth grade of SD Negeri Lamklat. The background of this study is based on the low level of students’ critical thinking skills, which is caused by teacher-centered learning processes and the lack of emphasis on problem-solving activities.This research employed a quantitative approach with a quasi-experimental design. The research design used was a pretest-posttest nonequivalent control group design. The population of this study consisted of all fifth-grade students of SD Negeri Lamklat, with samples divided into an experimental class and a control class. Data collection techniques included a critical thinking skills test and observation sheets. Data analysis was conducted using normality tests, homogeneity tests, and hypothesis testing using an independent sample t-test. The results of the study indicate that there is a significant effect of the implementation of the Problem Based Learning (PBL) model on students’ critical thinking skills. This is evidenced by the significance value obtained being greater than 0.05, leading to the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (H0). Therefore, it can be concluded that the Problem Based Learning (PBL) model is effective in improving students’ critical thinking skills in IPAS learning in the fifth grade of SD Negeri Lamklat.